Stealing each other's clothes. (Economist, 2001)
Sun Microsystems' struggle with IBM raises doubts about Sun's long-term strategy. On September 25, 2001, Sun launched its most powerful computer yet—the Sun Fire 15K—aimed at competing directly with the mainframe computers that dominate large companies' data centers. As the leading manufacturer of powerful server computers that run the Unix operating system, however, Sun risks being crushed between cheap servers running Microsoft's Windows NT and Linux, the free, open-source version of UNIX, at the low end and mainframes, which can now also run Linux, at the high end. Moreover, Sun's insistence on using its own processor chips, while the rest of the industry moves toward Intel's new Itanium chips, does not do the company any favors. Eventually, Sun will be forced to work out how to champion open standards without destroying its competitive advantage.